(untitled) (International Journal of Engineering and Computer Science, 2017)
In this paper we are presenting an overview of distributed system for wireless sensor network. In terms of computation, the WSN localization algorithms can be classified into centralized and distributed schemes. Further each category divided in to corresponding methods to solve localization problem. In the centralized scheme, sensor nodes send control messages to a central node whose location is known. In this paper we are showing what a distributed system and wireless sensor network and discuss the relation between distributed computing theory and sensor network applications